Metabolites and secretory immunoglobulins: messengers and effectors of the host–microbiota intestinal equilibrium - Goguyer-Deschaumes, Roman; Waeckel, Louis; Killian, Martin; Rochereau, Nicolas; Paul, Stéphane (Trends in immunology, 2022)
Maintaining commensal diversity is essential to host homeostasis, because microbial species provide a range of metabolic products and continuously educate the host immune system. The mucosal immune system must actively gather information about the composition of the microbiota, while offering an appropriate response. In mammals, bacterial sensing leads to the production of specific immunoglobulins (Ig), which reach the intestinal lumen as secretory Ig (SIg). Recent work has shed more light on the mechanisms by which SIg can shape bacterial repertoires and contribute to regulating host metabolism. In parallel, bacterial metabolites modulate Ig production and secretion. Here, we present an overview of the current knowledge of the relationship between bacterial metabolites and host SIg, correlating the disruption of this balance with chronic inflammation in humans. SIg participate in shaping the intestinal microbiota and facilitate elimination of fast-dividing strains while promoting colonization, fitness, cooperation, or metabolism of specific taxa.SIg-deficient mice display severe dysbiosis and chronic gut inflammation. In humans, patients who are IgA deficient (SIgAD) only display mild dysbiosis, perhaps because of SIgM compensation, but this remains conjectural.By tuning the composition and metabolism of the microbiota, SIg can modify the abundance and absorption of microbial-derived metabolites.Microbial-derived metabolites can modify SIg production. Tryptophan derivatives and secondary bile acids tend to reduce IgA production, whereas short-chain fatty acids have opposite effects depending on carbon chain length, concentration, and presence of cofactors derived from the microbiota.Not only inflammatory bowel disease (IBD), but also other extraintestinal diseases have correlated with impaired mucosal IgA responses and dysregulation of the microbiota metabolome.